The Effect of Takeover Protection in Quiet Life and Bonding Firms - Fich, Eliezer M.; Harford, Jarrad; Yore, Adam S. (Journal of Financial and Quantitative Analysis, 2025)
Abstract Antitakeover measures are controversial because the evidence of their net effect on shareholders is mixed. We propose that, for many firms, the potential bonding benefits outweigh the agency costs of the quiet life, explaining the mixed results. We study business combination and poison pill laws as exogenous shocks to takeover vulnerability and use shareholder valuation of internal slack as an indicator of the net effect of takeover protection. Firms susceptible to quiet life agency problems exhibit a decrease in the market-assessed value of internal slack. Conversely, cash appreciates at companies where takeover protection bonds commitments with major counterparties.